Plasma-immersion formation of high-intensity gaseous ion beams; Vacuum; Vol. 165 - Ryabchikov A. I. Aleksandr Ilyich; Sivin D. O. Denis Olegovich; Korneva O. S. Olga Sergeevna; Ananin P. S. Petr Semenovich; Bumagina A. I. Anna Ivanovna; Stepanov I. B. Igor Borisovich (2019, 2019)
Title screen